De novo DUOX2 expression in neutrophil subsets shapes the pathogenesis of intestinal disease - Ashish Singh; Marina Ainciburu; Kieran Wynne; Sajad A. Bhat; Alfonso Blanco; Ioanna Tzani; Yasutada Akiba; Stephen J. Lalor; Jonathan D. Kaunitz; Billy Bourke; Vincent P. Kelly; Glen Doherty; et al. (2025)
Infiltrating neutrophils are key effector cells in inflammatory bowel disease (IBD) while providing antimicrobial defense and tissue restitution in the intestine. The complexity of neutrophil functions in local environments underscores our limited understanding of how their adaptation in tissues influences disease progression. Here, we demonstrate that neutrophils recruited in murine colitis and infection models, idiopathic IBD, and chronic granulomatous disease-associated IBD undergo extensive transcriptional reprogramming, resulting in the emergence of neutrophil populations that feature unique DUOX2 NADPH oxidase expression. Functional studies utilizing mice with myeloid and neutrophil specific DUOX2 inactivation reveal a vital and dichotomous role for this NADPH oxidase in both colitis and intestinal infection. Niche-directed reprogramming promoted a DUOX2-dependent chemokine and cytokine-rich intestinal environment that amplified and prolonged inflammatory responses, suggesting that selectively suppressing DUOX2 may constitute an anti-inflammatory strategy for IBD treatment. Altering spatiotemporal redox signaling by de novo expression of a ROS-generating enzyme represents an important feature for functional neutrophil diversification in disease, with implications for other neutrophil-driven diseases in specialized niches.